Islam, civility and political culture - Milani, Milad; Adrahtas, Vassilios (New directions in Islam, 2021)
Introduction: Eschaton and civility in Islamic history / Milad Milani -- The quandary of modernity : Islam and civility / Milad Milani and Vassilios Adrahtas -- Islamic civility : narrative, habitus and institution / Armando Salvatore -- Good behaviour : Islam and Christianity as framework for religious life / Bryan S. Turner -- Considerations in Hadith and Qur'an : text and interpretation in a study of civility / Aisha Y. Musa -- The limits of Islamic civility in India / Prashant Keshavmurthy -- Islam divided : the underlying political culture of the conflict between the Sunni and the Shi'a / Vassilios Adrahtas and Milad Milani -- The paradox of gendered holiness in Islamic mysticism / Milad Milani and Marley Krok -- Conclusion: the prospect of an eschatological civility / Vassilios Adrahtas.